Identification of Factors that define Success or Failure in the Adoption of the SIG-UFRN Software Ecosystem - Oliveira, Sandro Ronaldo Bezerra; Vasconcelos, Ailson Medeiros (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Software Ecosystems (ECOS) emerge through interactions between actors around a technological platform focused on software products and services. The Integrated Management Systems of the Federal University of Rio Grande do Norte (SIG-UFRN), a technological platform that is part of the SIG-UFRN software ecosystem, are used by a considerable number of Federal Education Institutions (IFE) distributed across the Brazilian national territory. Problem: There are adoption scenarios for this ecosystem that define the situation of implementing the technological platform in IFEs, which enable success or failure in this process. These scenarios are determined by factors that need to be identified to clarify which reasons lead to the successful adoption of the ecosystem, as these factors, if not observed, can harm the business activities of IFEs, cause waste of resources and also lead to penalties for public managers for wrong decisions. Solution: Identify factors inherent to the technical, business and social aspects that lead to success or failure in the adoption of this ecosystem. IS Theory: This research is under the aegis of sociotechnical theory, as we intend to identify technical, business and social factors that can determine the success in adopting the SIG-UFRN software ecosystem. Method: The research is qualitative in nature, carried out through semi-structured interviews and analyzed using open and axial coding techniques of Grounded Theory. Summary of Results: Among the factors identified, we highlight Institutional Mobilization and Integration. Contributions and Impacts in the IS area: The contribution of this paper is to provide a set of factors that will serve as an element of analysis for public managers who wish to join the SIG-UFRN software ecosystem.